------------------------------------------------------------------------ -- Bag equivalence for lists ------------------------------------------------------------------------ {-# OPTIONS --without-K --safe #-} -- Note that this module is not parametrised by a definition of -- equality; it uses ordinary propositional equality. module Bag-equivalence where open import Equality.Propositional hiding (trans) open import Logical-equivalence hiding (id; _∘_; inverse) open import Prelude as P hiding (id; swap) open import Bijection equality-with-J using (_↔_; module _↔_; Σ-≡,≡↔≡) open import Equality.Decision-procedures equality-with-J open import Fin equality-with-J as Finite open import Function-universe equality-with-J as Function-universe hiding (_∘_; Kind; module Kind; bijection) open import H-level.Closure equality-with-J open import Injection equality-with-J using (_↣_) open import List equality-with-J open import Monad equality-with-J hiding (map) ------------------------------------------------------------------------ -- Any -- Any. Any : ∀ {a p} {A : Set a} (P : A → Set p) (xs : List A) → Set p Any P [] = ⊥ Any P (x ∷ xs) = P x ⊎ Any P xs -- Alternative definition of Any. data Any′ {a p} {A : Set a} (P : A → Set p) : List A → Set (a ⊔ p) where here : ∀ {x xs} → P x → Any′ P (x ∷ xs) there : ∀ {x xs} → Any′ P xs → Any′ P (x ∷ xs) -- The two definitions of Any are isomorphic. Any′-[] : ∀ {a p ℓ} {A : Set a} {P : A → Set p} → Any′ P [] ↔ ⊥ {ℓ = ℓ} Any′-[] {ℓ = ℓ} {P = P} = record { surjection = record { logical-equivalence = record { to = to ; from = from } ; right-inverse-of = λ p → ⊥-elim p } ; left-inverse-of = from∘to } where to′ : ∀ {xs} → Any′ P xs → [] ≡ xs → ⊥ {ℓ = ℓ} to′ (here p) = ⊥-elim ∘ List.[]≢∷ to′ (there p) = ⊥-elim ∘ List.[]≢∷ to : Any′ P [] → ⊥ to p = to′ p refl from = ⊥-elim from∘to′ : ∀ {xs} (p : Any′ P xs) ([]≡xs : [] ≡ xs) → subst (Any′ P) []≡xs (from (to′ p []≡xs)) ≡ p from∘to′ (here p) = ⊥-elim ∘ List.[]≢∷ from∘to′ (there p) = ⊥-elim ∘ List.[]≢∷ from∘to : ∀ p → from (to p) ≡ p from∘to p = from∘to′ p refl Any′-∷ : ∀ {a p} {A : Set a} {P : A → Set p} {x xs} → Any′ P (x ∷ xs) ↔ P x ⊎ Any′ P xs Any′-∷ {P = P} {x} {xs} = record { surjection = record { logical-equivalence = record { to = to ; from = from } ; right-inverse-of = [ (λ _ → refl) , (λ _ → refl) ] } ; left-inverse-of = from∘to } where to′ : ∀ {ys} → Any′ P ys → ys ≡ x ∷ xs → P x ⊎ Any′ P xs to′ (here p) ≡∷ = inj₁ (subst P (List.cancel-∷-head ≡∷) p) to′ (there p) ≡∷ = inj₂ (subst (Any′ P) (List.cancel-∷-tail ≡∷) p) to : Any′ P (x ∷ xs) → P x ⊎ Any′ P xs to p = to′ p refl from = [ here , there ] from∘to′ : ∀ {ys} (p : Any′ P ys) ≡∷ → from (to′ p ≡∷) ≡ subst (Any′ P) ≡∷ p from∘to′ (here p) ≡∷ with List.cancel-∷-head ≡∷ | List.cancel-∷-tail ≡∷ | sym (List.unfold-∷ ≡∷) from∘to′ (here p) .refl | refl | refl | refl = refl from∘to′ (there p) ≡∷ with List.cancel-∷-head ≡∷ | List.cancel-∷-tail ≡∷ | sym (List.unfold-∷ ≡∷) from∘to′ (there p) .refl | refl | refl | refl = refl from∘to : ∀ p → from (to p) ≡ p from∘to p = from∘to′ p refl Any↔Any′ : ∀ {a p} {A : Set a} {P : A → Set p} {xs} → Any P xs ↔ Any′ P xs Any↔Any′ {P = P} {[]} = ⊥ ↔⟨ inverse Any′-[] ⟩ Any′ P [] □ Any↔Any′ {P = P} {x ∷ xs} = P x ⊎ Any P xs ↔⟨ id ⊎-cong Any↔Any′ {P = P} ⟩ P x ⊎ Any′ P xs ↔⟨ inverse Any′-∷ ⟩ Any′ P (x ∷ xs) □ ------------------------------------------------------------------------ -- Lemmas relating Any to some basic list functions Any-++ : ∀ {a p} {A : Set a} (P : A → Set p) (xs ys : List A) → Any P (xs ++ ys) ↔ Any P xs ⊎ Any P ys Any-++ P [] ys = Any P ys ↔⟨ inverse ⊎-left-identity ⟩ ⊥ ⊎ Any P ys □ Any-++ P (x ∷ xs) ys = P x ⊎ Any P (xs ++ ys) ↔⟨ id ⊎-cong Any-++ P xs ys ⟩ P x ⊎ (Any P xs ⊎ Any P ys) ↔⟨ ⊎-assoc ⟩ (P x ⊎ Any P xs) ⊎ Any P ys □ Any-concat : ∀ {a p} {A : Set a} (P : A → Set p) (xss : List (List A)) → Any P (concat xss) ↔ Any (Any P) xss Any-concat P [] = id Any-concat P (xs ∷ xss) = Any P (xs ++ concat xss) ↔⟨ Any-++ P xs (concat xss) ⟩ Any P xs ⊎ Any P (concat xss) ↔⟨ id ⊎-cong Any-concat P xss ⟩ Any P xs ⊎ Any (Any P) xss □ Any-map : ∀ {a b p} {A : Set a} {B : Set b} (P : B → Set p) (f : A → B) (xs : List A) → Any P (map f xs) ↔ Any (P ∘ f) xs Any-map P f [] = id Any-map P f (x ∷ xs) = P (f x) ⊎ Any P (map f xs) ↔⟨ id ⊎-cong Any-map P f xs ⟩ (P ∘ f) x ⊎ Any (P ∘ f) xs □ Any->>= : ∀ {ℓ p} {A B : Set ℓ} (P : B → Set p) (xs : List A) (f : A → List B) → Any P (xs >>= f) ↔ Any (Any P ∘ f) xs Any->>= P xs f = Any P (concat (map f xs)) ↔⟨ Any-concat P (map f xs) ⟩ Any (Any P) (map f xs) ↔⟨ Any-map (Any P) f xs ⟩ Any (Any P ∘ f) xs □ Any-filter : ∀ {a p} {A : Set a} (P : A → Set p) (p : A → Bool) (xs : List A) → Any P (filter p xs) ↔ Any (λ x → P x × T (p x)) xs Any-filter P p [] = ⊥ □ Any-filter P p (x ∷ xs) with p x ... | true = P x ⊎ Any P (filter p xs) ↔⟨ inverse ×-right-identity ⊎-cong Any-filter P p xs ⟩ (P x × ⊤) ⊎ Any (λ x → P x × T (p x)) xs □ ... | false = Any P (filter p xs) ↔⟨ Any-filter P p xs ⟩ Any (λ x → P x × T (p x)) xs ↔⟨ inverse ⊎-left-identity ⟩ ⊥₀ ⊎ Any (λ x → P x × T (p x)) xs ↔⟨ inverse ×-right-zero ⊎-cong (_ □) ⟩ (P x × ⊥) ⊎ Any (λ x → P x × T (p x)) xs □ ------------------------------------------------------------------------ -- List membership infix 4 _∈_ _∈_ : ∀ {a} {A : Set a} → A → List A → Set _ x ∈ xs = Any (λ y → x ≡ y) xs -- Any can be expressed using _∈_. Any-∈ : ∀ {a p} {A : Set a} (P : A → Set p) (xs : List A) → Any P xs ↔ ∃ λ x → P x × x ∈ xs Any-∈ P [] = ⊥ ↔⟨ inverse ×-right-zero ⟩ (∃ λ x → ⊥₀) ↔⟨ ∃-cong (λ x → inverse ×-right-zero) ⟩ (∃ λ x → P x × ⊥) □ Any-∈ P (x ∷ xs) = P x ⊎ Any P xs ↔⟨ ∃-intro P x ⊎-cong Any-∈ P xs ⟩ (∃ λ y → P y × y ≡ x) ⊎ (∃ λ y → P y × y ∈ xs) ↔⟨ inverse ∃-⊎-distrib-left ⟩ (∃ λ y → P y × y ≡ x ⊎ P y × y ∈ xs) ↔⟨ ∃-cong (λ y → inverse ×-⊎-distrib-left) ⟩ (∃ λ y → P y × (y ≡ x ⊎ y ∈ xs)) □ -- Using this property we can prove that Any and _⊎_ commute. Any-⊎ : ∀ {a p q} {A : Set a} (P : A → Set p) (Q : A → Set q) (xs : List A) → Any (λ x → P x ⊎ Q x) xs ↔ Any P xs ⊎ Any Q xs Any-⊎ P Q xs = Any (λ x → P x ⊎ Q x) xs ↔⟨ Any-∈ (λ x → P x ⊎ Q x) xs ⟩ (∃ λ x → (P x ⊎ Q x) × x ∈ xs) ↔⟨ ∃-cong (λ x → ×-⊎-distrib-right) ⟩ (∃ λ x → P x × x ∈ xs ⊎ Q x × x ∈ xs) ↔⟨ ∃-⊎-distrib-left ⟩ (∃ λ x → P x × x ∈ xs) ⊎ (∃ λ x → Q x × x ∈ xs) ↔⟨ inverse $ Any-∈ P xs ⊎-cong Any-∈ Q xs ⟩ Any P xs ⊎ Any Q xs □ ------------------------------------------------------------------------ -- Bag and set equivalence and the subset and subbag orders -- Various kinds of relatedness. -- -- NOTE: Perhaps it would be better to define the subbag property in -- terms of embeddings, rather than injections. The HoTT book (first -- edition) claims that injectivity "is an ill-behaved notion for -- non-sets". open Function-universe public using (Kind) hiding (module Kind) module Kind where open Function-universe public using () renaming ( implication to subset ; logical-equivalence to set ; injection to subbag ; bijection to bag ; equivalence to bag-with-equivalence ) open Kind public -- A general definition of "relatedness" for lists. infix 4 _∼[_]_ _∼[_]_ : ∀ {a} {A : Set a} → List A → Kind → List A → Set a xs ∼[ k ] ys = ∀ z → z ∈ xs ↝[ k ] z ∈ ys -- Bag equivalence. infix 4 _≈-bag_ _≈-bag_ : ∀ {a} {A : Set a} → List A → List A → Set a xs ≈-bag ys = xs ∼[ bag ] ys -- Alternative definition of bag equivalence. infix 4 _≈-bag′_ record _≈-bag′_ {a} {A : Set a} (xs ys : List A) : Set a where field bijection : Fin (length xs) ↔ Fin (length ys) related : xs And ys Are-related-by bijection -- Yet another definition of bag equivalence. This definition is taken -- from Coq's standard library. infixr 5 _∷_ infix 4 _≈-bag″_ data _≈-bag″_ {a} {A : Set a} : List A → List A → Set a where [] : [] ≈-bag″ [] _∷_ : ∀ x {xs ys} (xs≈ys : xs ≈-bag″ ys) → x ∷ xs ≈-bag″ x ∷ ys swap : ∀ {x y xs} → x ∷ y ∷ xs ≈-bag″ y ∷ x ∷ xs trans : ∀ {xs ys zs} (xs≈ys : xs ≈-bag″ ys) (ys≈zs : ys ≈-bag″ zs) → xs ≈-bag″ zs ------------------------------------------------------------------------ -- Some congruence lemmas Any-cong : ∀ {k a p q} {A : Set a} {P : A → Set p} {Q : A → Set q} {xs ys : List A} → (∀ x → P x ↝[ k ] Q x) → xs ∼[ k ] ys → Any P xs ↝[ k ] Any Q ys Any-cong {P = P} {Q} {xs} {ys} P↔Q xs≈ys = Any P xs ↔⟨ Any-∈ P xs ⟩ (∃ λ z → P z × z ∈ xs) ↝⟨ ∃-cong (λ z → P↔Q z ×-cong xs≈ys z) ⟩ (∃ λ z → Q z × z ∈ ys) ↔⟨ inverse (Any-∈ Q ys) ⟩ Any Q ys □ ++-cong : ∀ {k a} {A : Set a} {xs₁ xs₂ ys₁ ys₂ : List A} → xs₁ ∼[ k ] ys₁ → xs₂ ∼[ k ] ys₂ → xs₁ ++ xs₂ ∼[ k ] ys₁ ++ ys₂ ++-cong {xs₁ = xs₁} {xs₂} {ys₁} {ys₂} xs₁∼ys₁ xs₂∼ys₂ = λ z → z ∈ xs₁ ++ xs₂ ↔⟨ Any-++ _ xs₁ xs₂ ⟩ z ∈ xs₁ ⊎ z ∈ xs₂ ↝⟨ xs₁∼ys₁ z ⊎-cong xs₂∼ys₂ z ⟩ z ∈ ys₁ ⊎ z ∈ ys₂ ↔⟨ inverse (Any-++ _ ys₁ ys₂) ⟩ z ∈ ys₁ ++ ys₂ □ map-cong : ∀ {k a b} {A : Set a} {B : Set b} (f : A → B) {xs ys : List A} → xs ∼[ k ] ys → map f xs ∼[ k ] map f ys map-cong f {xs} {ys} xs∼ys = λ z → z ∈ map f xs ↔⟨ Any-map _ f xs ⟩ Any (λ x → z ≡ f x) xs ↝⟨ Any-cong (λ x → z ≡ f x □) xs∼ys ⟩ Any (λ x → z ≡ f x) ys ↔⟨ inverse (Any-map _ f ys) ⟩ z ∈ map f ys □ concat-cong : ∀ {k a} {A : Set a} {xss yss : List (List A)} → xss ∼[ k ] yss → concat xss ∼[ k ] concat yss concat-cong {xss = xss} {yss} xss∼yss = λ z → z ∈ concat xss ↔⟨ Any-concat _ xss ⟩ Any (λ zs → z ∈ zs) xss ↝⟨ Any-cong (λ zs → z ∈ zs □) xss∼yss ⟩ Any (λ zs → z ∈ zs) yss ↔⟨ inverse (Any-concat _ yss) ⟩ z ∈ concat yss □ >>=-cong : ∀ {k ℓ} {A B : Set ℓ} {xs ys : List A} {f g : A → List B} → xs ∼[ k ] ys → (∀ x → f x ∼[ k ] g x) → (xs >>= f) ∼[ k ] (ys >>= g) >>=-cong {xs = xs} {ys} {f} {g} xs∼ys f∼g = λ z → z ∈ xs >>= f ↔⟨ Any->>= _ xs f ⟩ Any (λ x → z ∈ f x) xs ↝⟨ Any-cong (λ x → f∼g x z) xs∼ys ⟩ Any (λ x → z ∈ g x) ys ↔⟨ inverse (Any->>= _ ys g) ⟩ z ∈ ys >>= g □ filter-cong : ∀ {k a} {A : Set a} (p : A → Bool) (xs ys : List A) → xs ∼[ k ] ys → filter p xs ∼[ k ] filter p ys filter-cong p xs ys xs∼ys = λ z → z ∈ filter p xs ↔⟨ Any-filter _ p xs ⟩ Any (λ x → z ≡ x × T (p x)) xs ↝⟨ Any-cong (λ _ → _ □) xs∼ys ⟩ Any (λ x → z ≡ x × T (p x)) ys ↔⟨ inverse (Any-filter _ p ys) ⟩ z ∈ filter p ys □ ------------------------------------------------------------------------ -- More properties -- Bind distributes from the left over append. >>=-left-distributive : ∀ {ℓ} {A B : Set ℓ} (xs : List A) (f g : A → List B) → xs >>= (λ x → f x ++ g x) ≈-bag (xs >>= f) ++ (xs >>= g) >>=-left-distributive xs f g = λ z → z ∈ xs >>= (λ x → f x ++ g x) ↔⟨ Any->>= (_≡_ z) xs (λ x → f x ++ g x) ⟩ Any (λ x → z ∈ f x ++ g x) xs ↔⟨ Any-cong (λ x → Any-++ (_≡_ z) (f x) (g x)) (λ _ → id) ⟩ Any (λ x → z ∈ f x ⊎ z ∈ g x) xs ↔⟨ Any-⊎ (λ x → z ∈ f x) (λ x → z ∈ g x) xs ⟩ Any (λ x → z ∈ f x) xs ⊎ Any (λ x → z ∈ g x) xs ↔⟨ inverse (Any->>= (_≡_ z) xs f ⊎-cong Any->>= (_≡_ z) xs g) ⟩ z ∈ xs >>= f ⊎ z ∈ xs >>= g ↔⟨ inverse (Any-++ (_≡_ z) (xs >>= f) (xs >>= g)) ⟩ z ∈ (xs >>= f) ++ (xs >>= g) □ -- This property does not hold for ordinary list equality. ¬->>=-left-distributive : ¬ ({A B : Set} (xs : List A) (f g : A → List B) → xs >>= (λ x → f x ++ g x) ≡ (xs >>= f) ++ (xs >>= g)) ¬->>=-left-distributive distrib = Bool.true≢false true≡false where xs = true ∷ false ∷ [] f = λ x → x ∷ [] g = f eq : true ∷ true ∷ false ∷ false ∷ [] ≡ true ∷ false ∷ true ∷ false ∷ [] eq = distrib xs f g true≡false : true ≡ false true≡false = List.cancel-∷-head (List.cancel-∷-tail eq) -- _++_ is commutative. ++-comm : ∀ {a} {A : Set a} (xs ys : List A) → xs ++ ys ≈-bag ys ++ xs ++-comm xs ys = λ z → z ∈ xs ++ ys ↔⟨ Any-++ (_≡_ z) xs ys ⟩ z ∈ xs ⊎ z ∈ ys ↔⟨ ⊎-comm ⟩ z ∈ ys ⊎ z ∈ xs ↔⟨ inverse (Any-++ (_≡_ z) ys xs) ⟩ z ∈ ys ++ xs □ -- _++_ is idempotent (when set equivalence is used). ++-idempotent : ∀ {a} {A : Set a} (xs : List A) → xs ++ xs ∼[ set ] xs ++-idempotent xs = λ z → z ∈ xs ++ xs ↔⟨ Any-++ (_≡_ z) xs xs ⟩ z ∈ xs ⊎ z ∈ xs ↝⟨ ⊎-idempotent ⟩ z ∈ xs □ -- The so-called "range splitting" property (see, for instance, -- Hoogendijks "(Relational) Programming Laws in the Boom Hierarchy of -- Types"). range-splitting : ∀ {a} {A : Set a} (p : A → Bool) (xs : List A) → filter p xs ++ filter (not ∘ p) xs ≈-bag xs range-splitting p xs = λ z → z ∈ filter p xs ++ filter (not ∘ p) xs ↔⟨ Any-++ _ _ (filter (not ∘ p) xs) ⟩ z ∈ filter p xs ⊎ z ∈ filter (not ∘ p) xs ↔⟨ Any-filter _ p xs ⊎-cong Any-filter _ (not ∘ p) xs ⟩ Any (λ x → z ≡ x × T (p x)) xs ⊎ Any (λ x → z ≡ x × T (not (p x))) xs ↔⟨ inverse $ Any-⊎ _ _ xs ⟩ Any (λ x → z ≡ x × T (p x) ⊎ z ≡ x × T (not (p x))) xs ↔⟨ Any-cong (λ x → lemma (z ≡ x) (p x)) (λ x → x ∈ xs □) ⟩ z ∈ xs □ where lemma : ∀ {a} (A : Set a) (b : Bool) → A × T b ⊎ A × T (not b) ↔ A lemma A b = A × T b ⊎ A × T (not b) ↔⟨ ×-comm ⊎-cong ×-comm ⟩ T b × A ⊎ T (not b) × A ↔⟨ if-lemma (λ _ → A) id id b ⟩ A □ -- The so-called "range disjunction" property, strengthened to use the -- subbag preorder instead of set equivalence. range-disjunction : ∀ {a} {A : Set a} (p q : A → Bool) (xs : List A) → filter (λ x → p x ∨ q x) xs ∼[ subbag ] filter p xs ++ filter q xs range-disjunction p q xs = λ z → z ∈ filter (λ x → p x ∨ q x) xs ↔⟨ Any-filter _ (λ x → p x ∨ q x) _ ⟩ Any (λ x → z ≡ x × T (p x ∨ q x)) xs ↝⟨ Any-cong (λ x → lemma (z ≡ x) (p x) (q x)) (λ x → x ∈ xs □) ⟩ Any (λ x → z ≡ x × T (p x) ⊎ z ≡ x × T (q x)) xs ↔⟨ Any-⊎ _ _ _ ⟩ Any (λ x → z ≡ x × T (p x)) xs ⊎ Any (λ x → z ≡ x × T (q x)) xs ↔⟨ inverse (Any-filter _ p _ ⊎-cong Any-filter _ q _) ⟩ z ∈ filter p xs ⊎ z ∈ filter q xs ↔⟨ inverse $ Any-++ _ _ _ ⟩ z ∈ filter p xs ++ filter q xs □ where inj : (b₁ b₂ : Bool) → T (b₁ ∨ b₂) ↣ T b₁ ⊎ T b₂ inj true true = record { to = inj₁; injective = λ _ → refl } inj true false = record { to = inj₁; injective = ⊎.cancel-inj₁ } inj false true = record { to = inj₂; injective = ⊎.cancel-inj₂ } inj false false = record { to = λ (); injective = λ {} } lemma : ∀ {a} (A : Set a) (b₁ b₂ : Bool) → A × T (b₁ ∨ b₂) ↣ A × T b₁ ⊎ A × T b₂ lemma A b₁ b₂ = A × T (b₁ ∨ b₂) ↝⟨ id ×-cong inj b₁ b₂ ⟩ A × (T b₁ ⊎ T b₂) ↔⟨ ×-⊎-distrib-left ⟩ A × T b₁ ⊎ A × T b₂ □ ------------------------------------------------------------------------ -- The first two definitions of bag equivalence above are logically -- equivalent -- One direction follows from the following lemma, which states that -- list membership can be expressed as "there is an index which points -- to the element". -- -- As an aside, note that the right-hand side is almost -- index xs ⁻¹ z. ∈-index : ∀ {a} {A : Set a} {z} (xs : List A) → z ∈ xs ↔ ∃ λ i → z ≡ index xs i ∈-index {z = z} [] = ⊥ ↔⟨ inverse $ ∃-Fin-zero _ ⟩ (∃ λ (i : ⊥) → z ≡ index [] i) □ ∈-index {z = z} (x ∷ xs) = z ≡ x ⊎ z ∈ xs ↔⟨ id ⊎-cong ∈-index xs ⟩ z ≡ x ⊎ (∃ λ i → z ≡ index xs i) ↔⟨ inverse $ ∃-Fin-suc _ ⟩ (∃ λ i → z ≡ index (x ∷ xs) i) □ -- The index which points to the element. index-of : ∀ {a} {A : Set a} {z} {xs : List A} → z ∈ xs → Fin (length xs) index-of = proj₁ ∘ _↔_.to (∈-index _) -- For the other direction a sequence of lemmas is used. -- The first lemma states that ∃ λ z → z ∈ xs is isomorphic to Fin n, -- where n is the length of xs. Thierry Coquand pointed out that this -- is a generalisation of singleton-contractible. Fin-length : ∀ {a} {A : Set a} (xs : List A) → (∃ λ z → z ∈ xs) ↔ Fin (length xs) Fin-length xs = (∃ λ z → z ∈ xs) ↔⟨ ∃-cong (λ _ → ∈-index xs) ⟩ (∃ λ z → ∃ λ i → z ≡ index xs i) ↔⟨ ∃-comm ⟩ (∃ λ i → ∃ λ z → z ≡ index xs i) ↔⟨⟩ (∃ λ i → Singleton (index xs i)) ↔⟨ ∃-cong (λ _ → _⇔_.to contractible⇔↔⊤ (singleton-contractible _)) ⟩ Fin (length xs) × ⊤ ↔⟨ ×-right-identity ⟩ Fin (length xs) □ -- From this lemma we get that lists which are bag equivalent have -- related lengths. Fin-length-cong : ∀ {a} {A : Set a} {xs ys : List A} → xs ≈-bag ys → Fin (length xs) ↔ Fin (length ys) Fin-length-cong {xs = xs} {ys} xs≈ys = Fin (length xs) ↔⟨ inverse $ Fin-length xs ⟩ ∃ (λ z → z ∈ xs) ↔⟨ ∃-cong xs≈ys ⟩ ∃ (λ z → z ∈ ys) ↔⟨ Fin-length ys ⟩ Fin (length ys) □ abstract -- In fact, they have equal lengths. length-cong : ∀ {a} {A : Set a} {xs ys : List A} → xs ≈-bag ys → length xs ≡ length ys length-cong = _⇔_.to Finite.isomorphic-same-size ∘ Fin-length-cong -- All that remains (except for some bookkeeping) is to show that -- the isomorphism which Fin-length-cong returns relates the two -- lists. Fin-length-cong-relates : ∀ {a} {A : Set a} {xs ys : List A} (xs≈ys : xs ≈-bag ys) → xs And ys Are-related-by Fin-length-cong xs≈ys Fin-length-cong-relates {xs = xs} {ys} xs≈ys i = index xs i ≡⟨ proj₂ $ to (∈-index _) $ to (xs≈ys _) (from (∈-index _) (i , refl)) ⟩ index ys (proj₁ $ to (∈-index _) $ to (xs≈ys _) $ from (∈-index _) (i , refl)) ≡⟨ refl ⟩∎ index ys (to (Fin-length-cong xs≈ys) i) ∎ where open _↔_ -- We get that the two definitions of bag equivalence are logically -- equivalent. ≈⇔≈′ : ∀ {a} {A : Set a} {xs ys : List A} → xs ≈-bag ys ⇔ xs ≈-bag′ ys ≈⇔≈′ = record { to = λ xs≈ys → record { bijection = Fin-length-cong xs≈ys ; related = Fin-length-cong-relates xs≈ys } ; from = from } where equality-lemma : ∀ {a} {A : Set a} {x y z : A} → y ≡ z → (x ≡ y) ↔ (x ≡ z) equality-lemma refl = id from : ∀ {xs ys} → xs ≈-bag′ ys → xs ≈-bag ys from {xs} {ys} xs≈ys z = z ∈ xs ↔⟨ ∈-index xs ⟩ ∃ (λ i → z ≡ index xs i) ↔⟨ Σ-cong (_≈-bag′_.bijection xs≈ys) (λ i → equality-lemma $ _≈-bag′_.related xs≈ys i) ⟩ ∃ (λ i → z ≡ index ys i) ↔⟨ inverse (∈-index ys) ⟩ z ∈ ys □ ------------------------------------------------------------------------ -- Left cancellation -- We have basically already showed that cons is left cancellative for -- the (first) alternative definition of bag equivalence. ∷-left-cancellative′ : ∀ {a} {A : Set a} {x : A} xs ys → x ∷ xs ≈-bag′ x ∷ ys → xs ≈-bag′ ys ∷-left-cancellative′ {x = x} xs ys x∷xs≈x∷ys = record { bijection = Finite.cancel-suc (_≈-bag′_.bijection x∷xs≈x∷ys) ; related = Finite.cancel-suc-preserves-relatedness x xs ys (_≈-bag′_.bijection x∷xs≈x∷ys) (_≈-bag′_.related x∷xs≈x∷ys) } -- By the equivalence above we get the result also for the first -- definition of bag equivalence, but we can show this directly, with -- the help of some lemmas. abstract -- The index-of function commutes with applications of certain -- inverses. Note that the last three equational reasoning steps do -- not need to be written out; I included them in an attempt to make -- it easier to understand why the lemma holds. index-of-commutes : ∀ {a} {A : Set a} {z : A} {xs ys} → (xs≈ys : xs ≈-bag ys) (p : z ∈ xs) → index-of (_↔_.to (xs≈ys z) p) ≡ _↔_.to (Fin-length-cong xs≈ys) (index-of p) index-of-commutes {z = z} {xs} {ys} xs≈ys p = (index-of $ to (xs≈ys z) p) ≡⟨ lemma z p ⟩ (index-of $ to (xs≈ys _) $ proj₂ $ from (Fin-length xs) $ to (Fin-length xs) (z , p)) ≡⟨ refl ⟩ (index-of $ proj₂ $ Σ-map P.id (to (xs≈ys _)) $ from (Fin-length xs) $ to (Fin-length xs) (z , p)) ≡⟨ refl ⟩ (to (Fin-length ys) $ Σ-map P.id (to (xs≈ys _)) $ from (Fin-length xs) $ index-of p) ≡⟨ refl ⟩∎ (to (Fin-length-cong xs≈ys) $ index-of p) ∎ where open _↔_ lemma : ∀ z p → (index-of $ to (xs≈ys z) p) ≡ (index-of $ to (xs≈ys (index xs (to (Fin-length xs) (z , p)))) $ proj₂ $ from (Fin-length xs) $ to (Fin-length xs) (z , p)) lemma z p with to (Fin-length xs) (z , p) | Σ-≡,≡←≡ (left-inverse-of (Fin-length xs) (z , p)) lemma .(index xs i) .(from (∈-index xs) (i , refl)) | i | refl , refl = refl -- Bag equivalence isomorphisms preserve index equality. Note that -- this means that, even if the underlying equality is proof -- relevant, a bag equivalence isomorphism cannot map two distinct -- proofs of z ∈ xs (say) to different positions. index-equality-preserved : ∀ {a} {A : Set a} {z : A} {xs ys} {p q : z ∈ xs} (xs≈ys : xs ≈-bag ys) → index-of p ≡ index-of q → index-of (_↔_.to (xs≈ys z) p) ≡ index-of (_↔_.to (xs≈ys z) q) index-equality-preserved {z = z} {p = p} {q} xs≈ys eq = index-of (_↔_.to (xs≈ys z) p) ≡⟨ index-of-commutes xs≈ys p ⟩ _↔_.to (Fin-length-cong xs≈ys) (index-of p) ≡⟨ cong (_↔_.to (Fin-length-cong xs≈ys)) eq ⟩ _↔_.to (Fin-length-cong xs≈ys) (index-of q) ≡⟨ sym $ index-of-commutes xs≈ys q ⟩∎ index-of (_↔_.to (xs≈ys z) q) ∎ -- If x ∷ xs is bag equivalent to x ∷ ys, then xs and ys are bag -- equivalent. ∷-left-cancellative : ∀ {a} {A : Set a} {x : A} {xs ys} → x ∷ xs ≈-bag x ∷ ys → xs ≈-bag ys ∷-left-cancellative {A = A} {x} {xs} {ys} x∷xs≈x∷ys z = ⊎-left-cancellative (x∷xs≈x∷ys z) (lemma x∷xs≈x∷ys) (lemma (inverse ∘ x∷xs≈x∷ys)) where abstract -- If the equality type is proof irrelevant (so that p and q are -- equal), then this lemma can be proved without the help of -- index-equality-preserved. lemma : ∀ {xs ys} (inv : x ∷ xs ≈-bag x ∷ ys) → Well-behaved (_↔_.to (inv z)) lemma {xs} inv {b = z∈xs} {a = p} {a′ = q} hyp₁ hyp₂ = ⊎.inj₁≢inj₂ ( fzero ≡⟨ refl ⟩ index-of {xs = x ∷ xs} (inj₁ p) ≡⟨ cong index-of $ sym $ to-from hyp₂ ⟩ index-of {xs = x ∷ xs} (from (inj₁ q)) ≡⟨ index-equality-preserved (inverse ∘ inv) refl ⟩ index-of {xs = x ∷ xs} (from (inj₁ p)) ≡⟨ cong index-of $ to-from hyp₁ ⟩ index-of {xs = x ∷ xs} (inj₂ z∈xs) ≡⟨ refl ⟩∎ fsuc (index-of {xs = xs} z∈xs) ∎) where open _↔_ (inv z) -- Cons is not left cancellative for set equivalence. ∷-not-left-cancellative : ¬ (∀ {A : Set} {x : A} {xs ys} → x ∷ xs ∼[ set ] x ∷ ys → xs ∼[ set ] ys) ∷-not-left-cancellative cancel = _⇔_.to (cancel (++-idempotent (tt ∷ [])) tt) (inj₁ refl) -- _++_ is left and right cancellative (for bag equivalence). ++-left-cancellative : ∀ {a} {A : Set a} (xs : List A) {ys zs} → xs ++ ys ≈-bag xs ++ zs → ys ≈-bag zs ++-left-cancellative [] eq = eq ++-left-cancellative (x ∷ xs) eq = ++-left-cancellative xs (∷-left-cancellative eq) ++-right-cancellative : ∀ {a} {A : Set a} {xs ys zs : List A} → xs ++ zs ≈-bag ys ++ zs → xs ≈-bag ys ++-right-cancellative {xs = xs} {ys} {zs} eq = ++-left-cancellative zs (λ z → z ∈ zs ++ xs ↔⟨ ++-comm zs xs z ⟩ z ∈ xs ++ zs ↔⟨ eq z ⟩ z ∈ ys ++ zs ↔⟨ ++-comm ys zs z ⟩ z ∈ zs ++ ys □) ------------------------------------------------------------------------ -- The third definition of bag equivalence is sound with respect to -- the other two -- _∷_ preserves bag equivalence. infixr 5 _∷-cong_ _∷-cong_ : ∀ {a} {A : Set a} {x y : A} {xs ys} → x ≡ y → xs ≈-bag ys → x ∷ xs ≈-bag y ∷ ys _∷-cong_ {x = x} {xs = xs} {ys} refl xs≈ys = λ z → z ≡ x ⊎ z ∈ xs ↔⟨ id ⊎-cong xs≈ys z ⟩ z ≡ x ⊎ z ∈ ys □ -- We can swap the first two elements of a list. swap-first-two : ∀ {a} {A : Set a} {x y : A} {xs} → x ∷ y ∷ xs ≈-bag y ∷ x ∷ xs swap-first-two {x = x} {y} {xs} = λ z → z ≡ x ⊎ z ≡ y ⊎ z ∈ xs ↔⟨ ⊎-assoc ⟩ (z ≡ x ⊎ z ≡ y) ⊎ z ∈ xs ↔⟨ ⊎-comm ⊎-cong id ⟩ (z ≡ y ⊎ z ≡ x) ⊎ z ∈ xs ↔⟨ inverse ⊎-assoc ⟩ z ≡ y ⊎ z ≡ x ⊎ z ∈ xs □ -- The third definition of bag equivalence is sound with respect to -- the first one. ≈″⇒≈ : ∀ {a} {A : Set a} {xs ys : List A} → xs ≈-bag″ ys → xs ≈-bag ys ≈″⇒≈ [] = λ _ → id ≈″⇒≈ (x ∷ xs≈ys) = refl ∷-cong ≈″⇒≈ xs≈ys ≈″⇒≈ swap = swap-first-two ≈″⇒≈ (trans xs≈ys ys≈zs) = λ z → _ ↔⟨ ≈″⇒≈ xs≈ys z ⟩ ≈″⇒≈ ys≈zs z -- The other direction should also be provable, but I expect that this -- requires some work.